An Analysis On Slang In The Script Of 8-Mile Film: A Sociolinguistic Approach - Widyanto, Cahyo Anjar; , Drs. H. Maryadi, M.A; , Titis Setyabudi, S.S., M. Hum (2013)
This research discusses the syntactic forms of slang expressions in the script of 8-mile film, the kind of meanings of slang expression in the script of 8-mile film and the reasons of using slang expression in the script of 8-mile film.This research is a qualitative research. The data are taken from document analysis. The object of the study is analyzing the slang in the script of 8-mile film: Sociolinguistic approach.The results of the study, 1) there are only found 3 syntactic forms in 8-mile film that are: word ( single word and compound word), slang phrase, and acronym. The frequency of use and the percentage of use that are: there are found 10 single word or about 62,5% of all the data. Compound word has one data, or 6,3% of all the data. Slang phrase has 4 data or about 25% of all the data while slang acronym has only 1 datum or about 63% of all the data. 2) There are only found 2 kinds of meaning of using slang word in 8-mile film, denotative and connotative. The frequency of use and the percentage of use that are: there are 2 denotative meaning data or about 12,5% of all the data. Connotative meaning has 14 data, or about 87,5% of all the data. 3) There are only found 4 reasons of using slang word in 8-mile film that are: To exuberance of spirit and the sheer joy of living or the exhilaration of the moment, Connotative (spontaneous), to escape from cliches-an intention usually arises from impatience with existing words and phrases, to enrich the language, and to intimate, maybe to prove, that one belongs or has belonged to a certain school or university, trade or profession, or social class; artistic, literary, or musical set, or cultured group or stratum. The frequency of use and the percentage of use that are: as spontenous data, or about 18,7% of all the data. To escape from cliches has 8 data, or 50% of all the data. To enrich the language has 2 data or about 12,5% of all the data while to intimate, maybe to prove, that one belongs or has belonged to a certain school or university, trade or profession, or social class, has only 3 datum or about 18,7% of all the data.